(untitled) (Saúde Ética & Justiça, 2017)
The dentistry in occupational health isn't much implement, and although it's important, it isn't participating of worker health programs nowadays. The authors suggest an occupational dentistry program in partnership with occupational medicine for improving the life quality. The occupational dentistry program will permit to make an epidemiological statistical investigation in dentistry and the influence of the labour environment in the oral cavity. With these datum will be possible to recommend improvement and/or environment control with standart of individual or general security. The statistical investigation will permit to know the size of dental service for the company and how to stablish a dental accord to treatment workers and their dependents. Throught institutional campaigns it will be possible to give dental specifical orientation for pregnants and children in order to stablish preventive dentistry actions. The occupational surgeon dentistry has as a priority the prevention of the oral diseases to advise the curative dentistry about all curative activities.